2011
DOI: 10.1007/s12253-011-9423-6
|View full text |Cite
|
Sign up to set email alerts
|

p53 Binds to Estrogen Receptor 1 Promoter in Human Breast Cancer Cells

Abstract: p53 is a tumor suppressor protein that regulates estrogen receptor 1 (ESR1) expression. To investigate the mechanism of ESR1 gene regulation by p53, chromatin immunoprecipitation was applied to assess the binding of p53, DNMT1, HDAC1 and MeCP2 to both silenced ESR1 promoter in MDA-MB-468 cells and active ESR1 promoter in MCF-7 breast cancer cells. The results of chromatin immunoprecipitation experiments showed that p53 protein binds to both unmethylated CpG island of the ESR1 promoter in the ER-positive MCF-7 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
15
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 34 publications
6
15
0
2
Order By: Relevance
“…43 Others suggest MeCP2 and p53 may have feedback regulation. 44 Our results show that Clbn has a physical interaction with a transcriptional repressor of p53 (our unpublished data). Clbn may export transcription suppressors from nucleus upon DNA damage, releases suppression to p53, which needs more study.…”
Section: Discussionsupporting
confidence: 54%
“…43 Others suggest MeCP2 and p53 may have feedback regulation. 44 Our results show that Clbn has a physical interaction with a transcriptional repressor of p53 (our unpublished data). Clbn may export transcription suppressors from nucleus upon DNA damage, releases suppression to p53, which needs more study.…”
Section: Discussionsupporting
confidence: 54%
“…Besides the E2 levels, the PvuII 'C' allele was also associated with decreased levels of androstenedione (Weiderpass et al, 2000). Based on these observations, we believe that the ESR-α gene polymorphisms may indirectly influence the binding activity to the hormone response element on the target gene by regulating gene expression or receptor function, and then influence the transcriptional regulation of it's downstream genes including TP53 (Rasti et al, 2012), causing the origination of the breast cancer.…”
Section: Discussionmentioning
confidence: 84%
“…4). This result, while unexpected, is not unparalleled, as a number of studies have shown that mutant p53 protein is capable of binding to its target gene sequences and regulating their expression (Pan and Haines, 2000;O'Farrell et al, 2004;Weisz et al, 2007;Chandrachud and Gal, 2009;Perez et al, 2010;Rasti et al, 2012). Since the mutant p53 did not associate with the 14-3-3s promoter in the absence of plakoglobin (SCC9 cells), this suggests a role for plakoglobin in associating p53 with its target gene promoter(s).…”
Section: Discussionmentioning
confidence: 84%